The Role of Service Robots in the Global Market - Pogosyan, Rima (Bulletin of Yerevan University G: Economics, 2024)
The article presents possible approaches to the classification of robots and the scope of their application. In a broad sense, dividing the robotics market into production and service robotics, we see that, despite the fact that production robotics is a predominant part of the global robotics market; it has been experiencing what can be said to be static growth at the expense of its field for many years. As for service robotics, it can be stated that in recent years there has been rapid growth in this area. This circumstance is determined by several principles. First of all, this is determined by the creation and distribution of new types of personal service robots, which are used in people’s everyday life and make it easier. In this sense, one can distinguish between robotic vacuum cleaners, kitchen robots, robotic assistants (robots that provide care for the elderly or disabled) and others. As for professional service robotics, it can be noted that the conditions of bans and isolation due to the Coronavirus epidemic also served as an incentive for the development of this area. In this situation, for example, the need for robot consultants in stores or robots delivering food and medicine has come to the fore. This trend continued even after the pandemic ended.
Keywords: robot; robotics; service robots; innovation; patent; intellectual property